How does the use of anticoagulants influence the outcome of elderly thoraci̇c trauma patients? (Annals of Medical Research, 2023)
Aim: As a result of the demographic transition, an increasing number of elderly patients require therapeutic anticoagulation for a variety of comorbidities. These individuals need multidisciplinary care because they frequently use many drugs, have concomitant conditions, and have functional status that is already compromised.Materials and Methods: A total of 103 trauma patients over the age of 65 who were admitted to the emergency department due to thoracic trauma were evaluated according to Gender, trauma etiology and characteristics, comorbidities, antithrombolytic therapy use, rib and sternum fracture, hemothorax, pneumothorax, and contusion due to thoracic trauma.Results: There were 72 male patients and 31 female patients with the average age of 73.8 +/- 8.61 years (min: 65, max: 96). The rates of hemothorax, pneumothorax, hemopneumothorax, contusion, atelectasis, and pneumonia were not significantly different between patients using and not using antithrombolytics (respectively, p = 0.666, p = 0.320, p = 0.212, p = 0.369, p = 0.633, p = 0.652). Comorbid conditions or using antithrombolytics had no impact on how long patients stayed in the hospital (p = 0.503, p = 0.814). The only predictor that significantly increased the length of stay was determined to be the tube thoracostomy (p = 0.001).Conclusion: Antithrombolytic usage had no impact on hemothorax, pneumothorax, or contusion development. However, further research and implementation initiatives are required in order to completely integrate geriatric principles into the care of older persons who have experienced trauma.
Keywords: Thoracic trauma; Geriatric population; Geriatric trauma; Older people; Trauma; Rib fracture